?SYNTHESIS AND CARDIOVASCULAR ACTIVITY OF NEW PHENOTHIAZINES (Biological Sciences - PJSIR, 1996)
Some new Schiffs bases substituted-benzaldehyde, 2-(2-acetyl-lOH-phenothiazin-I0-yl)-2-oxo-ethyl hydrazones (Iva-IVe), 2-acetyl-l 0-(5-substituted phenyJ-2-oxo-4-thiazoJidin-I-yl)-aminoacetylphenothiazines (Va-ve), 2-acetyl- I0-[(2-oxo-3-chloro-4-azetidin-l-yl) aminoacetylphenothiazines (VIa-VIe) and I, 3-disubstituted phenyl-5-[(2-acetyl- 1O-phenothiazin-I 0-yl)-2-oxo-ethyJ] formazans (Vlla-Vllb) have been synthesized and were evaluated for their car- diovascular activity. Compounds Iv a, Ivd and IVe showed highly statistically significant changes in blood pressure, heart rate and pressor responses (Cardiovascular activity). The most active compound in our preliminary study is found to be 2, 4-dichlorobenzaldehyde 2-(2-acetyl-1 OH-phenothiazin-I0-yl)-2-oxo-ethyl hydrazone (IVa) which showed statistically significant changes in the fall of blood pressure (75.63%).